ADJUNCT SYNBIOTIC THERAPY WITH VILDAGLIPTIN-METFORMIN IMPROVES GLYCEMIC CONTROL, INSULIN SENSITIVITY, AND COST-EFFICIENCY IN ELDERLY PATIENTS WITH TYPE 2 DIABETES - KALA P; JAMUNA RANI R; SRUTHI ANIL KUMAR AH (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: This study evaluated the efficacy of daily synbiotic supplementation combined with vildagliptin-metformin therapy for enhancing glycemic management, insulin responsiveness, and treatment cost-effectiveness in elderly type 2 diabetes patients. Methods: A 12-week randomized, open-label, parallel-group clinical trial was conducted at a tertiary care teaching hospital in India. Participants aged 60–80 years with stable vildagliptin-metformin therapy were randomly assigned (1:1) to either continue standard treatment alone or receive additional daily synbiotic capsules containing 109 colony forming units each of Lactobacillus and Bifidobacterium species with fructo-oligosaccharides. Primary endpoints included changes in glycated hemoglobin (HbA1c), fasting blood glucose (FBG), postprandial blood glucose (PPBG), and triglyceride-glucose (TyG) index. Secondary outcomes assessed safety profile, treatment compliance, and cost per 1% HbA1c reduction using t-tests and repeated-measures ANOVA (α=0.05). Results: A total of 210 participants completed the study (n=105 per group). The synbiotic-supplemented group demonstrated significantly greater improvements compared to standard therapy: HbA1c reduction (−1.2% vs. −0.6%), FBG reduction (−29.9 vs. −15.2 mg/dL), PPBG reduction (−39.8 vs. −21.2 mg/dL), and TyG index improvement (−0.47 vs. −0.21) (all p<0.001). Treatment adherence exceeded 90% in both groups. Mild gastrointestinal effects occurred more frequently with synbiotic supplementation (27.6% vs. 21.0%) but were transient with no serious adverse events reported. Cost analysis favored the synbiotic intervention (₹750 vs. ₹900/1% HbA1c reduction). Conclusion: Among elderly type 2 diabetes patients receiving vildagliptin-metformin therapy, adjunctive synbiotic supplementation provided significant improvements in glycemic control and insulin sensitivity with superior cost-effectiveness and acceptable safety profile. These findings support considering synbiotic therapy integration in routine diabetes management when target glycemic goals remain unachieved.